2010
DOI: 10.1152/ajpheart.00451.2010
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 induces EMMPRIN expression in primary cardiomyocytes via JNK/Sp1 signaling and MMP-9 in part via EMMPRIN and through AP-1 and NF-κB activation

Abstract: and the extracellular matrix metalloproteinase (MMP) inducer (EMMPRIN) stimulate the expression of proinflammatory cytokines and MMPs and are elevated in myocardial hypertrophy, remodeling, and failure. Here, we report several novel findings in primary cardiomyocytes treated with IL-18. First, IL-18 activated multiple transcription factors, including NF-B (p50 and p65), activator protein (AP)-1 (cFos, cJun, and JunD), GATA, CCAAT/enhancer-binding protein, myocyte-specific enhancerbinding factor, interferon reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 52 publications
(73 reference statements)
7
73
1
Order By: Relevance
“…Mechanisms of regulation of endogenous CD147 expression are not well established, although several growth factors and cytokines have been shown to increase CD147 levels in a variety of contexts (Hagemann et al, 2005;Menashi et al, 2003;Reddy et al, 2010;Rucci et al, 2010). Previous studies have shown that Src is a crucial regulator of invadopodia formation (Murphy and Courtneidge, 2011), and a recent study showed that the Src family kinase, Fyn kinase, induces emmprin expression (Ramos and Dang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of regulation of endogenous CD147 expression are not well established, although several growth factors and cytokines have been shown to increase CD147 levels in a variety of contexts (Hagemann et al, 2005;Menashi et al, 2003;Reddy et al, 2010;Rucci et al, 2010). Previous studies have shown that Src is a crucial regulator of invadopodia formation (Murphy and Courtneidge, 2011), and a recent study showed that the Src family kinase, Fyn kinase, induces emmprin expression (Ramos and Dang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-a increases MMP-9 promoter activity in plasmids, likely through activator protein-1, nuclear factor k-light-chain-enhancer of activated B cells, or specificity protein-1 (Sato et al, 1993). Likewise, interleukins such as interleukin-17 and -18 induce MMP-9 expression via nuclear factor k-light-chain-enhancer of activated B cells and activator protein-1 pathways (Reddy et al, 2010).…”
Section: Inflammation and Mmps In Vvsmentioning
confidence: 99%
“…41,42 Overexpression of IL-18 in cardiomyocytes also induced activation of multiple transcription factors, including NF-B and IFN regulatory factor-1. 43 Data increasingly support an important role of IL-18 in mediating aspects of adverse cardiac remodeling.…”
Section: Cytokinesmentioning
confidence: 99%